KEDUDUKAN HUKUM WHISTLE BLOWER DALAM PERSPEKTIF HUKUM PIDANA DI INDONESIA - Hasbi, Mhd. (UNES Law Review, 2023)
One of the efforts made by the state in order to realize legal protection for every citizen is to carry out honest and fair law enforcement, including the state's efforts to and overcome the occurrence of criminal acts that can disrupt public security and public order. Current criminal law enforcement practices This is known as a new term, namely whitsle blower. Etymologically whitsle blower comes from the word whitsle which means "whistle" or "whistle sound", while blower means whistle blower or reporter, secret leaker, or whistleblower. The existence of the whitsle blower is very important in uncovering serious and organized criminal acts, especially crimes Corruption crimes have not received adequate legal protection. This can be seen from a number of cases of criminalization of whistleblowers by law enforcers. This research is normative research. research carried out by examining the literature using a statute approach. Regulation of whitsle blowers and justice collaborations in SEMA Number 04 of 2011. The role of whitsle blowers in Indonesia needs to continue to be encouraged and socialized, also implemented, both by government institutions, private companies and public institutions . Although the practice of protecting whitsle blowers is not without challenges, amidst the lack of protection for whitsle blowers in Indonesia, a whitsle blower can be threatened because of their reports or testimony regarding alleged violations and crimes that have occurred.